THE IMPACT OF THE FINANCIAL CRISIS ON CURRENT ACCOUNT SUSTAINABILITY IN LITHUANIA - Grajauskas, Rokas (Ekonomika, 2014)
Abstract. The paper deals with the dynamics of Lithuania’s current account in two distinct periods – the period in the run-up to the 2008–2009 financial crisis and the period since the crisis. The two main goals of the paper are: 1) to assess the sustainability of the level of Lithuania’s current account in the period 1995–2015 using an empirical model based on the intertemporal optimisation approach, and 2) to identify the factors behind the observed trends in Lithuania’s current account in the two periods in question. The research has been conducted using the methods of empirical (regression) analysis, theoretical explanations, and descriptive analysis. The paper finds that the current account in Lithuania has been sustainable since 1995, except for two brief periods – the 1999 Russian crisis and in 2009 when Lithuania’s economy contracted by more than 15% in real terms due to the global financial crisis. The empirical research has also revealed a shift in the level of the sustainable current account in the post-crisis period but shows an existing gap between the sustainable and the actual current account in Lithuania. Considering the characteristics of Lithuania’s economy, the paper concludes that the actual level of the current account in Lithuania is not optimal from the intertemporal point of view. Key words: intertemporal optimisation, current account, deleveraging, rebalancing, capital flight